2019
DOI: 10.1111/ajo.13027
|View full text |Cite
|
Sign up to set email alerts
|

Vascular balloon occlusion and planned caesarean hysterectomy for morbidly adherent placenta: A systematic review

Abstract: Background Morbidly adherent placenta is potentially life‐threatening, often requiring technically difficult surgery and large blood loss. Use of intravascular balloon occlusion with or without hysterectomy to reduce blood loss is increasing despite associated morbidity and lack of evidence of efficacy. Aims To evaluate if prophylactic use of vascular balloon occlusion at the time of planned caesarean hysterectomy for antenatally diagnosed morbidly adherent placenta reduces blood loss and transfusion requireme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Other procedures, such as vascular balloon occlusion, hypogastric artery ligation, and uterine tamponade, have been used in some patients 22,23 . One study with extensive patient participation in which balloon occlusion was performed indicated that the need for hysterectomy decreased with increasing obstetric experience in this subject 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Other procedures, such as vascular balloon occlusion, hypogastric artery ligation, and uterine tamponade, have been used in some patients 22,23 . One study with extensive patient participation in which balloon occlusion was performed indicated that the need for hysterectomy decreased with increasing obstetric experience in this subject 24 .…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies reported the efficacy of using an occlusive balloon during surgical management of MAP in reducing blood loss, with the highest efficacy in the aortic balloon [7]. We report the use of an intraoperative aortic balloon occlusion (IABO) procedure for bleeding control in Gravida Patients with Placenta Accreta in our center.…”
Section: Introductionmentioning
confidence: 97%